Eksistensi Ekstrakulikuler dan Konstribusinya dalam Peningkatan Strandart Kompetensi Lulusan di SMAN 2 Lamongan - Moch. Faizin Muflich; Rokim Rokim (Universitas Islam Lamongan, 2021)
In accordancevwith the Regulationvof the Minister ofvNational Education Number 62 of 2014 concerning Extracurricular, it states that the development of the potentialvof students asvreferred to invthe goals ofvnational educationvcan bevrealized through extracurricular activities. Extracurricular deals with student interests outside of their formal fields. As in SMADA Lamongan, there are several extracurricular activities including; recitation of the Koran, PMR, pencak silat, flag raising troops, scholarly romance magazines, creative working groups, cooperatives, choirs, theater, drum bands, dance, information technology etc. This clearly has an impact on the students who follow. Extracurricular deals with student interests outside of their formal fields. As in SMADA Lamongan, there are several extracurricular activities including; recitation of the Koran, PMR, pencak silat, flag raising troops, scholarly romance magazines, creative working groups, cooperatives, choirs, theater, drum bands, dance, information technology etc. This clearly has an impact on the students who follow. For this reason, extracurricular activities are also needed in improving the competence of graduates which includesvthree dimensions, namely the attitude dimension, the dimension ofvknowledge and the dimension of skills. Students cannot apply the knowledge they have acquired in class to their daily lives.